2020
DOI: 10.5585/remark.v18i4.13898
|View full text |Cite
|
Sign up to set email alerts
|

The relation between financial attitude, consumer purchasing behavior and debt background

Abstract: Purpose of the study: To estimate the degree of relationships between financial attitude, materialism, consumption by status, and consumer perception of the chosen payment method, and impacts on indebtedness.Methodology / approach: We used the survey technique, which collected data from 161 respondents. The quantitative data obtained were analyzed through structural equation modeling, as well as conditional mediation and moderation tests.Main results: Individuals with weak financial attitudes tend to be more m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
4
0
2
Order By: Relevance
“…This triggers individuals to use the internet to engage in social media if they do not want to be behind the times (Zhang, 2014). In addition, the emergence of various payment devices, such as e-money, will provide more convenience for individuals when they make transactions (Ritchie, 2022;Xavier et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This triggers individuals to use the internet to engage in social media if they do not want to be behind the times (Zhang, 2014). In addition, the emergence of various payment devices, such as e-money, will provide more convenience for individuals when they make transactions (Ritchie, 2022;Xavier et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…En el contexto actual, existe un discurso generalizado sobre la falta de dinero para honrar el compromiso, formar ahorros, realizar inversiones, convirtiéndose así en una especie de acumulación de cuentas y conduciendo a la realidad del endeudamiento. Según Piccini y Pinzetta (2014) citado en Xavier et al, (2019), el endeudamiento surge del consumo excesivo, en el que el ser humano adquiere deudas, implica expresamente sus ingresos mensuales y no cumple con sus compromisos financieros. En este escenario, debido a su capacidad (o incapacidad) para conducir su vida financiera es el desafío entre el éxito y el fracaso del presupuesto personal y familiar.…”
Section: Endeudamientounclassified
“…En este escenario, debido a su capacidad (o incapacidad) para conducir su vida financiera es el desafío entre el éxito y el fracaso del presupuesto personal y familiar. En este sentido, según Xavier et al, (2019) el endeudamiento se da cuando el individuo adquiere una deuda con la promesa de un futuro pago.…”
Section: Endeudamientounclassified
“…Other studies have found attitudes toward debt vary depending on gender, age, parents’ views and even education. For example, one study found that people with weak financial attitudes are more materialistic and are more prone to take on debt (Xavier et al , 2019). Another study reported that consumer attitudes about debt are linked to an understanding of debt and their skills navigating debt, and that those with stronger debt skills are less risk averse because they feel a sense of control over debt (Białowolski et al , 2018).…”
Section: Literature Reviewmentioning
confidence: 99%